Microvascular regulatory role and increased expression of vascular endothelial growth factor receptor type 2 in experimental gingivitis. (7th September 2012) - Gyurkovics, M.; Lohinai, Z.; Győrfi, A.; Bodor, C.; Székely, A. D.; Dinya, E.; Rosivall, L.
<x xml:space="preserve">Abstract</x> Objective The aim of the present study was to investigate the possible microvascular regulatory role of vascular endothelial growth factor receptor type 2 (VEGFR2) in experimental gingivitis in rats. Background Our previous results demonstrated that functionally active VEGFR2s are located in the venules of rat gingiva. While there is no remarkable endogenous gingival VEGF production under normal circumstances, exogenous VEGF, via VEGFR2, shows venodilatory effects. We assumed that VEGF plays an important role in vasoregulatory processes (vasodilation, increased permeability, angiogenesis) of gingival inflammation. Methods Gingivitis was induced by placing ligatures and composite material around and between the lower incisors of anesthetized Wistar rats next to the gingival margin. Seven days later, VEGFR2 antagonist (ZM323881), was dripped upon the labial gingiva next to the lower incisors. Diameter changes of the selected gingival venules were measured by vital microscopy. Animals with healthy gingiva served as controls. Venule diameter changes were compared to the baseline and to control groups (no ligature). Immunohistochemical and Western blot analysis for VEGFR2 were utilized. Results After 15, 30 and 60 min of local application of ZM323881, there was a significant venoconstriction in the inflamed gingiva compared to the baseline, while no change was recorded in controls. Endothelium, smooth muscle cells and pericytes of the gingivitis group showed increased VEGFR2 expression. Conclusion Our findings suggest that there is an increased VEGF production in gingivitis, which may play an important role in vasodilation of rat gingival venules.